Spremljanje utrjevanja lepila z dielektrično analizo - Šernek, Milan (Les (Ljubljana), 2004)
Adhesive cure monitoring is carried out for optimizing press schedule. Several analytical techniques are available for monitoring the cure of an adhesive (DSC, DMA, DTA), but not many could be successfully applied in industrial environment. A few methods have been developed for in-process purpose and most promising is dielectric analysis, which allows continuous in situ measurements. This article presents principles of dielectric analysis and describes a model for adhesive cure kinetics. The results of monitoring the cure of urea-formaldehyde adhesive are shown.
Keywords: lepila; utrjevanje; dielektrične lastnosti